If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10t + -8 = 12t Reorder the terms: -8 + 10t = 12t Solving -8 + 10t = 12t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12t' to each side of the equation. -8 + 10t + -12t = 12t + -12t Combine like terms: 10t + -12t = -2t -8 + -2t = 12t + -12t Combine like terms: 12t + -12t = 0 -8 + -2t = 0 Add '8' to each side of the equation. -8 + 8 + -2t = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -2t = 0 + 8 -2t = 0 + 8 Combine like terms: 0 + 8 = 8 -2t = 8 Divide each side by '-2'. t = -4 Simplifying t = -4
| 3x-5=3x+10 | | -12=m+4 | | 6(2x+7)=102 | | 6(x+2)=-12 | | z+1.1z+2.4=-0.6(2+5) | | -10-5x=-25 | | (1)=2x+5 | | u+.6666u-1.5=.8333(u-1.25) | | w+(w+4)=100 | | 3m+4p=8 | | x-21=-45 | | 3-4(-2+x)=11+3x | | 5x+9.3=4.8 | | x-45=56 | | -5x+2=-38 | | 2(2v+14)=-3(4v+14) | | 100+10x=15x | | 5-7x=-79 | | x+45=62 | | 3x=9(x-4) | | 5m-3=2 | | -1-3x=20 | | T^3+6t^2+-2+-12=0 | | 7x+9y=17 | | 3f-2=7 | | s^6-s^5-s^3+s^4=0 | | 7x^2+14x+21=0 | | 9x+20=7x | | 9x-12(6)=30 | | 5m-3=2m-9 | | -4(4+r)=12+3r | | x^2-5x+55=8605 |